2016
DOI: 10.3892/br.2016.824
|View full text |Cite
|
Sign up to set email alerts
|

Circulating osteocyte-derived exosomes contain miRNAs which are enriched in exosomes from MLO-Y4 cells

Abstract: Abstract. Signaling molecules produced by osteocytes have been proposed to serve as soluble factors that contribute to bone remodeling, as well as to homeostasis of other organs. However, to the best of our knowledge, there are currently no studies investigating the role of osteocyte-secreted exosomes. In the present study, ablation of osteocytes in mice [osteocyte-less (OL)] was used to examine the microRNA (miRNA) levels of plasma-circulating exosomes. In order to investigate the function of osteocyte-secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 34 publications
0
67
0
Order By: Relevance
“…Exosome micro (mi)RNAs, the main molecules playing a regulatory role in exosomes, primarily cause gene silencing in receptor cells (Sato, et al , 2017). A mechanism of the transfer of exosome‐shuttle miRNAs among DCs was previously documented as a means of communication and post‐transcriptional regulation (Montecalvo, et al , 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Exosome micro (mi)RNAs, the main molecules playing a regulatory role in exosomes, primarily cause gene silencing in receptor cells (Sato, et al , 2017). A mechanism of the transfer of exosome‐shuttle miRNAs among DCs was previously documented as a means of communication and post‐transcriptional regulation (Montecalvo, et al , 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Many of the proteins identified in this paper have also been identified in a proteomic analysis of osteoblast released EVs [31, 52]. A previous in vivo study has suggested a role for EVs in systemic signalling, demonstrating altered miRNA expression in EVs isolated from the plasma of osteocyte ablated mice and wild-type mice [24], while other studies have demonstrated the potential for EVs in therapeutics to enhance osteogenic gene expression [53], the use of drug loaded EVs for osteoporosis therapies [27], and the use of EVs for functionalisation of TE scaffolds to enhance bone regeneration [54, 55]. In addition to osteocyte derived MAEVs and the contents driving MSC osteogenesis, MAEVs may also act as sites for mineral nucleation, as has previously been demonstrated in osteoblast EVs [56, 57].…”
Section: Discussionmentioning
confidence: 86%
“…Interestingly, it has recently been shown that bone cells release EVs and utilise these vesicles as a mechanism to mediate osteoblast and stem/stromal cell osteogenesis [2023]. Moreover, osteocyte-derived EVs contain miRNAs known to mediate osteoblast function, highlighting a potential non-protein based role in bone cell communication [24, 25]. Bone derived EVs may also be exploited as a potential therapy for various diseases, as well as having potential for treatment of critical size bone defects [26].…”
Section: Introductionmentioning
confidence: 99%
“…Sato et al compared osteocyte-secreted exosomes and circulating exosomes from osteocyte-less mice. The results indicated that ablation of osteocytes in mice alters the miRNA levels of plasma exosomes (57). This study linked osteocyte exosomes to circulating exosomes, which provides the concept that osteocyte-derived exosomes may transfer their components to other organs.…”
Section: Paracrine Role Of Bone-derived Evsmentioning
confidence: 82%